DEVELOPMENT AND VALIDATION OF A NEW KNOWLEDGE, ATTITUDE, PRACTICE AND STIGMA QUESTIONNAIRE ON TUBERCULOSIS IN MALAYSIA - Zakaria, Rosnani; Wan Mohamad, Wan Mohd Zahiruddin; Nik Husain, Nik Rosmawati; Wan Mansor, Wan Nor Arifin; Idris, Nur Aiza; Mohd Zain, Norhasmah; Zakaria, Norhidayah; Ishak, Azlina (Malaysian Journal of Public Health Medicine, 2023)
There are challenges in controlling TB in Malaysia among young adults. To understand young adults’ knowledge, attitudes, practices, and stigma regarding TB, a valid and reliable measurement instrument must be developed and validated. We aim to develop and validate a new questionnaire about knowledge, attitudes, practices, and stigma regarding TB (KAPS-TB) for the young populations in Malaysia. Between the year 2017 and 2020, a cross-sectional study was conducted in two phases to validate KAPS-TB. Phase 1 involved 236 participants from secondary school students in Kelantan and Phase 2 involved 364 students from Health Campus, Universiti Sains Malaysia in Kelantan. KAPS-TB comprised sociodemographic characteristics and KAPS (knowledge, attitude, practice and stigma respectively). The knowledge section was analysed by the two-parameter logistic item response theory. Exploratory factor analysis and confirmatory factor analysis were used to explore the construct and reliability of items for the attitude and stigma sections. Validated KAPS-TB comprised 22, 5, 6 and 11 items on knowledge, attitude, practice and stigma, respectively. Overall, the results showed that each section presented valid and reliable items. KAPS-TB provides a valid and reliable instrument that could also be used to examine the effects of TB health education among the young population and to improve TB prevention and control.